The role of small RNAs in vegetative shoot development. (February 2016) - Fouracre, Jim P; Poethig, R Scott
Highlights: sRNA networks are key regulators of diverse aspects of vegetative growth. Increasing evidence suggests multiple developmental roles for certain sRNAs. The extent of quantitative regulation and translational repression are key unknowns. Abstract : Shoot development consists of the production of lateral organs in predictable spatial and temporal patterns at the shoot apex. To properly integrate such programs of growth across different cell and tissue types, plants require highly complex and robust genetic networks. Over the last twenty years, the roles of small, non-coding RNAs (sRNAs) in these networks have become increasingly apparent, not least in vegetative shoot growth. In this review, we describe recent progress in understanding the contribution of sRNAs to the regulation of vegetative shoot growth, and outline persisting experimental limitations in the field.